Temporalities—Technologies—Transgressions: Notes On Contemporary Slovak Poetry - Hostová, Ivana (Porównania, 2020)
In the course of the past three decades, marked in post-communist Central European countries by their sudden repositioning on the geopolitical map, Slovak social and cultural spaces, in great haste and chaos, got to locale-specific grips with postmodernism and, more or less simultaneously, entered contemporaneity. The leap to the present has created inherently transcultural modes of existence, in which global news, fashions and tastes form a relevant part of individuals’ identities. Through the prism of Peter Osborne’s (2013, 2018) concept of historical contemporaneity, this essay briefly outlines modifications that the segment of Slovak poetry marked by Osbornian contemporaneity has undergone in the past three decades.